Career termination in elite sport: A mixed retrospective-prospective longitudinal study over 12 years - Schmid, J.; Conzelmann, A.; Küttel, A.; Engel, R.; Schmid, M. J. (16th European Congress of Sport & Exercise Psychology (FEPSAC) Padova, 2022)
The end of their athletic career can be a difficult time for elite athletes, requiring thoughtful preparation and adjustment. We investigated the complex relationships between individual preconditions, transition characteristics, and consequences of athletic career termination. In a retrospective-prospective design, we surveyed 290 (former) elite athletes at two measurement points about the following: satisfaction with their ongoing sporting career (t1), athletic identity (t1), self-esteem (t1, t2), transition characteristics of their career end (t2), sporting success (t2), and emotional reactions, adjustment in terms of duration, quality, and extent of adjustment to career termination (t2). Results of structural equation modelling (SEM) revealed that neither sporting success nor career satisfaction had a direct effect on adjustment. However, retirement planning and athletic identity predicted extent of adjustment, which in turn predicted duration and quality of adjustment, and lastly self-esteem. Timeliness, voluntariness, and perception of gain predicted emotional reactions, which in turn predicted duration of adjustment. Emotional reactions and extent of adjustment mediated between preconditions and characteristics of career termination and self-esteem. While self-esteem after career termination was predominantly predicted by self-esteem 12 years earlier, perceived quality of adjustment to career termination had an influence on it. Compared to more traditional analysis techniques in previous research (e.g., ANOVA), using SEM provides a more valid picture of the interplay between individual preconditions of career termination, transition characteristics, and its consequences. This is particularly true with respect to the role of athletic identity and retirement planning - two aspects that support programs should pay special attention to.